Biochars and activated carbons as adsorbents of inorganic and organic compounds from multicomponent systems – A review - Gęca, Marlena; Wiśniewska, Małgorzata; Nowicki, Piotr (Advances in colloid and interface science, 2022)
Biochars are obtained by biomass pyrolysis, whereas activated carbon is a biochar that has undergone chemical or physical activation. Owing to the large surface area and easy surface modification both solids are widely applied as adsorbents. They are low-costs materials, they could be regenerated and their disposal is not troublesome. Adsorption of heavy metals, dyes, pharmaceuticals on the surface of biochars and activated carbons, from simple systems of adsorbate containing only one compound, are described extensively in the literature. The present paper provides an overview of reports on adsorption of inorganic and organic compounds onto these two types of adsorbents from the mixed adsorbate systems. The described adsorbate systems have been divided into those consisting of: two or more inorganic ions, two or more organic compounds and both of them (inorganic and organic ones). The research of this type is carried out much less frequently due to the more complicated description of interactions in the mixed adsorbate systems. [Display omitted] •Simultaneous adsorption of inorganic and organic compounds are reported.•Biochars and activated biocarbons as hazardous substances adsorbents were applied.•Heavy metal removal from their mixed solution was described.•Adsorption of dyes from the multi-component solutions was investigated.•The mutual synergistic and antagonistic actions depend on adsorbate and solid surface properties.